Sprężysto-Plastyczne Ugięcia Prętów Słabo Zakrzywionych o Dowolnym Przekroju - Orkisz, J. (Engineering Transactions, 1966)
The paper concerns the application of the method of substitute "multipoint sections" described in Refs. [5, 6, 8] for approximate computation of the elastic-plastic deflection of a bar of weak curvature. This method consists in replacing the given section of the bar by a "multipoint section" (Fig. 1) composed of "concentrated flanges". This enables, for a perfect elastic-plastic body, and a body with sectional linear strain hardening, the obtainment of a linear, therefore the simplest possible relation between the bending moment or the longitudinal force and the curvature of the bar (cf. (2.1)), independently of the form of its cross-section. The equations of small elastic-plastic deflections of straight bars obtained in Ref. [8] and the corresponding equations for large deflections obtained in Ref. [9] are generalized in the present paper to the case of bars with weak (constant) curvature. As a result are obtained simple equations resembling the former ones and describing the deformed bar.